2017
DOI: 10.1504/ijtel.2017.10003119
|View full text |Cite
|
Sign up to set email alerts
|

The relationship among pre-service teachers computer competence, attitude towards computer-assisted education, and intention of technology acceptance

Abstract: Use of technology takes time and requires a paradigm change for teachers to adopt it. Teachers' readiness, how they behave and perceive technology integration or adoption process is particularly critical. The current study investigates the relationship among pre-service teachers' computer competence, attitude towards computer-assisted education, and intention of technology acceptance. The results indicate that computer ownership, the internet access and amount of daily computer use do not correlate with the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 31 publications
3
12
2
4
Order By: Relevance
“…The government is still focused on providing technology tools and facilities. They consider technology integration to take place automatically when technology is available (Baturay et al, 2017;Ertmer, 1999;Niederhauser & Lindstrom, 2018). Specifically, it can be seen from the "Smart City" program from the Aceh Province government.…”
Section: Interpretation Of Interaction Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…The government is still focused on providing technology tools and facilities. They consider technology integration to take place automatically when technology is available (Baturay et al, 2017;Ertmer, 1999;Niederhauser & Lindstrom, 2018). Specifically, it can be seen from the "Smart City" program from the Aceh Province government.…”
Section: Interpretation Of Interaction Effectsmentioning
confidence: 99%
“…The results of the study showed that teachers who have a negative or neutral attitude towards the technology integration influenced by their knowledge and skills. They do not have sufficient knowledge and technology skills to integrate or choose the right technology into their learning activities (Baturay, Gökçearslan, & Ke, 2017;Buabeng-Andoh, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Scholars, teachers and curriculum developers worldwide wonder how to organize effective learning, and they arrive at the conclusion that development of informational skills in the information-educational environment of today is not only important but essential. Among other matters, their investigations concern the age in which it is advisable to start using electronic teaching aids in education (Alkhawaldeh, Hyassat, Al-Zboon, & Ahmad, 2017;Pasterk & Bollin, 2017), selection of information content (Bulman & Fairlie, 2016), building an individual learning trajectory for schoolchildren (Lapenok et al, 2016), introducing elements of remote learning in school (Nakayama, de Almeida, & Vicari, 2004), required level of a teacher's proficiency in computer technologies (Baturay, Gokcearslan, & Ke, 2017). https://dx.doi.org/10.15405/epsbs.2019.02.02.48 Corresponding Author: Irina Dobrotina Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 444 Scholars discuss what learning that meets informational and educational needs of today's schoolchildren should look lie if we want it to help students build cognitive independence in the information space (Ivanova, 2016).…”
Section: Research Questionsmentioning
confidence: 99%
“…Accelerate the construction of "double-qualified" teaching staff, speed up the introduction of the corresponding "double teacher" teacher construction, assessment and incentive programs can greatly promoted the enthusiasm of teachers to strengthen their own building, the number of "double-qualified" teachers gradually increased while the quality of teachers is obviously improved [8]. Scholars also actively discussed the concept, existing problems, construction measures and assessment standards of "dual-qualified" teachers.…”
Section: Status Of Teachers' Construction In Applied Universitiesmentioning
confidence: 99%
“…They should integrate teacher resources within and outside the school. Broaden sources of professional teachers actively introduce the community, business professionals into professional education, the establishment of a combination of high-level and application-oriented teachers [8]. In short, the construction of applied faculty is the need of school development, the need of cultivating applied undergraduate talents, and the need of cultivating students' innovative ability and practical ability.…”
Section: Strengthen the Training Of Teachers' Innovative Ability And mentioning
confidence: 99%